Islamic House Financing in Pakistan: A Demand Analysis - Muhammad Mansoor Javed; Muhammad Mahmmod Shah Khan; Haris Aslam (Islamic Banking and Finance Review, 2015)
his paper analyzes the issue of the nature of demand for house financing offered by Islamic banks in the Pakistan. The paper also identifies the factors that impact demand for house financing offered by Islamic banks. The study used survey data based on convenient face to face interview of 243 respondents. The study regressed conventional demand for Islamic house financing on six regressors: Shariah compliance, convenience, bank features, product features, social influence and knowledge. The study reveals that the nature of demand for Islamic house financing is conventional. The results of the study also indicate that religious factor negatively affect the demand for Islamic house financing whereas all other factors affect it positively. The study will help managers of Islamic banks to increase their market share in house financing by focusing on those factors which significantly affect the demand for their product.